Teaching Writing of Descriptive Text by Using Scaffolding Technique - Prabandani, Wahyu Nita (English Education:Journal of English Teaching and Research, 2016)
Writing is one of productive skill in learning English. Students must produce their own written texts. In teaching writing, the teacher needs a technique or media to support their teaching. One of the techniques that the teacher can be used is scaffolding. The purpose of this study are to know the students’ response and students’ problem in teaching writing of descriptive text by using scaffolding, the advantages and disadvantages of scaffolding technique. The approach of this research is qualitative and the design is descriptive qualitative. To get the data, the writer did observation, gave questionnaire to the students to know how the students’ response, interview to the English teacher, and took some pictures for documentation